Outrage [videorecording (DVD)] - Porto, R. F. I.; Poste, Marlene; Gayet, Julie, 1972-; Kane, Adelaide, 1990-; Sanders, Jay O., 1953-; Schick, Clemens, 1972- (Freestyle Digital Media, 2024)
In a secluded French chateau, a group of elite media and political personalities gather for a private dinner party. Beneath the glitz and glamor lie dark conspiracies between an extremist group and a prominent broadcast news company. As Ivy, a level-headed reporter, begins to unravel the tangled web of secrets, the partygoers realize that they have stumbled into a deadly trap. At the center of it all sits an unassuming mother with a mysterious agenda and revenge on the mind. The partygoers must not only fight for the truth, but for their lives.